The Portuguese Registry of Hypertrophic Cardiomyopathy: Overall results - Cardim, N (2018)
Introduction: We report the results of the Portuguese Registry of Hypertrophic Cardiomyopathy, an initiative that reflects the current spectrum of cardiology centers throughout the territory of Portugal. Methods: A direct invitation to participate was sent to cardiology departments. Baseline and outcome data were collected. Results: A total of 29 centers participated and 1042 patients were recruited. Four centers recruited 49% of the patients, of whom 59% were male, and mean age at diagnosis was 53±16 years. Hypertrophic cardiomyopathy (HCM) was identified as familial in 33%. The major reason for diagnosis was symptoms (53%). HCM was obstructive in 35% of cases and genetic testing was performed in 51%. Invasive septal reduction therapy was offered to 8% (23% of obstructive patients). Most patients (84%) had an estimated five-year risk of sudden death of <6%. Thirteen percent received an implantable cardioverter-defibrillator. After a median follow-up of 3.3 years (interquartile range [P25-P75] 1.3-6.5 years), 31% were asymptomatic. All-cause mortality was 1.19%/year and cardiovascular mortality 0.65%/year. The incidence of heart failure-related death was 0.25%/year, of sudden cardiac death 0.22%/year and of stroke-related death 0.04%/year. Heart failure-related death plus heart transplantation occurred in 0.27%/year and sudden cardiac death plus equivalents occurred in 0.53%/year. Conclusions: Contemporary HCM in Portugal is characterized by relatively advanced age at diagnosis, and a high proportion of invasive treatment of obstructive forms. Long-term mortality is low; heart failure is the most common cause of death followed by sudden cardiac death. However, the burden of morbidity remains considerable, emphasizing the need for disease-specific treatments that impact the natural history of the disease.